A risk management framework for distributed scrum using PRINCE2 methodology - Mohammad Esteki; Taghi Javdani Gandomani; Hadi Khosravi Farsani (Institute of Advanced Engineering and Science, 2020)
The distributed Agile development approach has been accepted by software companies due to its promised benefits. However, due to the controversial nature of distributed and Agile development, significant challenges arise from spatial, temporal, social, and cultural differences between distributed teams. Scrum, as the most popular Agile methodology, assumes that team members work together in the same room. But this principle does not apply in a realistic scenario where Scrum teams are distributed in different locations. Hence, proposing a risk management framework is necessary in order to succeed such teams. The purpose of this research was to propose a risk management framework in Scrum using the PRINCE2 methodology, which includes the perceived risks in distributed Scrum projects and their causes and roots for managing these risks. By embedding distributed Scrum in delivery layer of PRINCE2 and considering perceived risk factors, along with a hybrid model, a risk management framework was suggested. This framework has been used in a case study, and the results showed its proper functionality in detecting and eliminating potential risks in the case under study. Also, using this framework led to higher team efficiency in terms of increasing the number of completed user stories in each sprint.